PENDIRIAN USAHA KEDAI KOPI SEBAGAI UPAYA PENINGKATAN NILAI TAMBAH PRODUK PADA KEBUN KOPI SUKAHURIP CIANJUR - Rezkitaputri, Ajeng; Br Sebayang, Veralianta (Jurnal Manajemen Agribisnis Terapan, 2025)
Sukahurip Organic Coffee Plantation has experienced a decline in income due to low profit margins and has minimum product value added. This study aims to design the establishment of a coffee shop to ensure business sustainability by identifying consumer characteristics, analyzing consumer preferences, analyzing product value added, and analyzing business feasibility. The methods used include conjoint method, Hayami method, and business feasibility analysis. The results show that consumers prefer affordable coffee with a balanced flavor profile in terms of acidity and body. The value-added analysis indicates that all product variants provide more than 70% value added and over 90% profit. Non-financial aspects also support the business feasibility, with a strategic location and clearly defined target market. Financial aspects coffee shop business is deemed feasible, with an NPV of Rp383.948.160, IRR of 44%, a net B/C ratio of 3,01 (>1), a gross B/C ratio of 1,35 (>1), and a payback period of 5,55 years. The switching value analysis shows the business remains feasible even under a revenue decline of up to 26,172%, an arabica and robusta bean price increase of up to 245,36% and 278%.